Вклад доминирующих видов рода Cymbella Ag. (Bacillariophyta) в микрофитобентос Южного Байкала - Родионова, Е.В.; Помазкина, Г.В. (Альгология, 2006)
Приведены результаты многолетнего изучения рода Cymbella Ag. в литоральной зоне Южного Байкала. Оценена роль видов рода в продукционных процессах литоральной зоны. Изучены особенности их зонального распределения, сезонная и межгодовая динамика. Показана роль представителей рода в сообществах микрофитобентоса. На основе многолетних наблюдений охарактеризованы некоторые особенности экологии видов рода Cymbella. Long-term data on studies of the genus Cymbella in the littoral zone of Lake Baikal are discussed in the paper. Morphological characteristics of dominant representatives have been described. The role of the genus species in processes of the littoral zone has been estimated. Peculiarities of zonal distribution, seasonal and interannual dynamics and the role of these representatives in microphytobenthos communities are under discussion. Some characteristics of ecology of the genus species are described on the basis of long-term observations.